Blind SNR estimation based on cyclostationarity - HUA Meng; ZHU Jin-kang; GONG Ming (Tongxin xuebao)
Upsampling and shaping filtering introduce the cyclostationarity of transmit signals. Based on the cyclosta-tionary statistics of signals, a blind SNR estimator in AWGN channel was proposed. This estimator had no restrict on modulation mode and no need for transmitter to transmit known data. Simulation results show this estimator yields better performance than other classic blind SNR estimators, such as M2M4 and SVR estimators in a large SNR domain. Also, in order to show the absolute levels of performance, the simulated performance was compared to a Cramer-Rao lower bound.